Analisis kesalahan mahasiswa dalam menyelesaikan soal pada materi statistika berdasarkan teori Newman - Jelyani Feronika; Nurendah Yulianti; Sarah Inayah; Ahmad Lutfi; Husnul Khatimah Rusyid; Ahmad Mukhibin (Journal on Mathematics Education Research (J-MER), 2023)
The purpose of this research is to describe the types of mistakes made by students in solving problems based on Newman's theory on statistical material. The type of research used is descriptive research with a quantitative approach. The subjects of this study consisted of 9 Level 1 Mathematics Education students at Suryakancana University. The data collection technique in this study was a written test, with a test instrument consisting of 3 statistical questions in the form of descriptions. The percentage of types of errors made by students at the stage of reading the problem was found to be 20%, comprehension the problem was 20%, transformation was 20%, processing skills was 20%, and encoding was 20%. The types of errors in this study were analyzed using Newman's theory, namely 1) Errors in Reading Problems, 2) Errors in Understanding Problems, 3) Errors in Transformation, 4) Errors in Process Skills, and 5) Errors in Writing Final Answers. Of the 9 students it was found that the most common types of mistakes made by students in solving statistical problems were errors at the stage of understanding the problem and encoding errors.